2014
DOI: 10.1007/s10803-014-2229-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Specificity of Motor Impairments in Catching and Balance in Children with Autism

Abstract: To evaluate evidence for motor impairment specificity in autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD). Children completed performance-based assessment of motor functioning (Movement Assessment Battery for Children: MABC-2). Logistic regression models were used to predict group membership. In the models comparing typically developing and developmental disability (DD), all three MABC sub-scale scores were significantly negatively associated with having a DD. In the models co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
109
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 38 publications
12
109
0
5
Order By: Relevance
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
“…Many studies addressed this question with movement assessment batteries with normative percentiles for performance and objective scoring: for example, the PANESS (Dowell et al, 2009;Dziuk et al, 2007;Floris et al, 2016;Jansiewicz et al, 2006;Mostofsky, Burgess, & Gidley Larson, 2007), the M-ABC or M-ABC2 (Ament et al, 2015;Green, Baird et al, 2002;Green, Moore, & Reilly, 2002;Green et al, 2009;Hanaie et al, 2013;Hanaie et al, 2014;Kopp, Beckung, & Gillberg, 2010;McPhillips, Finlay, Bejerot, & Hanley, 2014;Miyahara et al, 1997;Sumner et al, 2016;Whyatt & Craig, 2012), or the Bruininks-Oseretsky test (Dewey et al, 2007;Ghaziuddin & Butler, 1998;Hilton, Zhang, Whilte, Klohr, & Constantino, 2012;Pan, 2014). These measures yield total scores which were sometimes analysed alone, but they each assess a range of fine and gross motor skills, including balance and gait, hopping or jumping, repetitive sequential movements of the hands and feet, manual dexterity and ball skills (catching and throwing).…”
mentioning
confidence: 99%
See 3 more Smart Citations